ANALISIS IMPLEMENTASI KONSEP GREEN INDUSTRY UNTUK PEMBELAJARAN LINGKUNGAN HIDUP YANG BERKELANJUTAN DI SDIT GUNUNG JATI KOTA TANGERANG - Anggreni, Elysa Vonia; Huliatunisa, Yayah; Nuraeni , Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Green Industry concept in sustainable environmental learning at SDIT Gunung Jati, Tangerang City. This research employed a qualitative approach with a descriptive method. Data were collected through observation, semi-structured interviews, and documentation involving the principal, teachers, students, and supporting school documents related to environmental programs. The data were analyzed through data reduction, data display, and conclusion drawing and verification. Data validity was ensured through technique triangulation, member checking, and comparison between field data and research findings. The results showed that the implementation of the Green Industry concept was reflected in several school programs and habits, including the non-plastic policy, the habit of bringing personal drinking bottles and food containers, greening activities, organic and inorganic waste sorting, the application of the 3R principles, composting, a healthy canteen, and water and electricity-saving practices. Sustainable environmental learning was implemented through the integration of environmental materials into classroom learning, direct practice, teacher role modeling, and a school culture that supports environmentally responsible behavior. These findings indicate that the Green Industry concept can be adapted in elementary education as a strategy to develop students’ environmental awareness and character. This study recommends strengthening planning, evaluation, and program sustainability so that Green Industry implementation is not merely a routine activity but becomes an integrated part of the school learning system.